Economic forecasting in Singapore: The Covid-19 experience - CHOW-TAN, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2023)
This Special Feature considers how accurately professional forecasters have predicted GDP growth and inflation in Singapore, especially during rare events such as the Global Financial Crisis (GFC) and COVID-19. It also illustrates the value of forecast probability distributions in inferring forecasters’ uncertainty when making predictions, and the degree of consensus between projections from different forecasters. The authors find that one-year ahead forecast errors for GDP growth and inflation increased during the GFC and the COVID-19 pandemic. While professional forecasters did not appear to have followed the Government’s forecasts when predicting growth during the GFC, they may have exhibited ”leader-following” behaviour when forecasting growth and inflation during COVID-19. Similarly, forecasters appear to exhibit herding behaviour during both crises. During the pandemic, moreover, the rise in forecast uncertainty was traced to a more volatile economic policy environment. Collectively, the paper’s results suggest that inflation expectations were well-anchored throughout the sample period.